2006
DOI: 10.1111/j.1601-183x.2006.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor polymorphisms and haplotypes associated with chronic fatigue syndrome

Abstract: Chronic fatigue syndrome (CFS) is a significant public health problem of unknown etiology, the pathophysiology has not been elucidated, and there are no characteristic physical signs or laboratory abnormalities. Some studies have indicated an association of CFS with deregulation of immune functions and hypothalamicpituitary-adrenal (HPA) axis activity. In this study, we examined the association of sequence variations in the glucocorticoid receptor gene (NR3C1) with CFS because NR3C1 is a major effector of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 53 publications
3
52
0
Order By: Relevance
“…NR3C1 has been implicated as regulator of the hypothalamic-pituitary-adrenal axis (18) and of the immune function: the increase in its ligand affinity has led to a reduction in T cell numbers and to a change in susceptibility to Supervised SNP selection in chronic fatigue syndrome autoimmune diseases (19). A higher frequency of the NR3C1_11159943 major allele has also been reported in patients with chronic fatigue syndrome (20). Moreover, the model associated the syndrome with the minor allele of 5HTT_7911132, a SNP that belongs to a gene that decreases the level of active serotonin when the allelic variants with increased transcriptional activity are present (21).…”
Section: Discussionmentioning
confidence: 99%
“…NR3C1 has been implicated as regulator of the hypothalamic-pituitary-adrenal axis (18) and of the immune function: the increase in its ligand affinity has led to a reduction in T cell numbers and to a change in susceptibility to Supervised SNP selection in chronic fatigue syndrome autoimmune diseases (19). A higher frequency of the NR3C1_11159943 major allele has also been reported in patients with chronic fatigue syndrome (20). Moreover, the model associated the syndrome with the minor allele of 5HTT_7911132, a SNP that belongs to a gene that decreases the level of active serotonin when the allelic variants with increased transcriptional activity are present (21).…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by the different degree of fatigue in investigated patients and this theory rules in favor of genetic predisposition. On the other hand, immune reaction releases IL-6, which increases the quantity of free circulating cortisol by stimulating the hypothalamus CRH neurons and inhibiting the corticosteroid-building globulin gene (CBG) (26). All of this links CFS with possible hereditary disorders, including cortisol transport and CBG gene mutation as well as glucocorticoid resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Variance in the expression of genes associated with HPA axis function has been found to be associated with ME/CFS [44][45][46]. For example, Rajeevan and colleagues [47] found that those with certain cortisol regulatory mechanisms (i.e., a single nucleotide polymorphism in the glucocorticoid receptor (GR) gene) were at increased risk for ME/CFS. Others have also found differences in the expression of glucocorticoid receptor NR3C1 in individuals with ME/CFS as compared to controls [33].…”
Section: Hypothalamic-pituitary-adrenal (Hpa) Axis Dysfunctionmentioning
confidence: 99%